Media representation of Operation Al-Aqsa Flood in Arab and Western outlets: a critical discourse analysis - Mohammed, Awham Rashid; Ashinida Aladdin; Azianura Hani Shaari (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study examines the contrasting media coverage of Operation Al-Aqsa Flood to uncover the ideological underpinnings of the accounts presented by Al-Jazeera and CNN. It examines how the two leading media outlets report the same event from essentially contradictory viewpoints, thereby mirroring wider geopolitical divides. The study compares the narratives and examines the ideological parameters which shape the conflict reporting. It also employs Fairclough’s three- dimensional approach to conduct a textual, discursive and sociocultural analysis of the context embedded in media reporting. Besides, the study conducts a qualitative content analysis of Al-Jazeera and CNN news reports and evaluates the narratives to explain the differences in the representation and inherent bias. The study design employs qualitative content analysis of broadcast news reports released by both Al-Jazeera and CNN, as well as a comparative evaluation of the narratives to explain variations in representations and inherent biases. The findings show that CNN reporting is characterized by violence- and hostility-focused language that frames the event as a legitimate use of force. However, Al-Jazeera’s coverage places the emphasis on the themes of liberation and resistance. CNN’s ideological bias reflects the Western geopolitical interests and Israeli sympathies, while Palestinian actions are discursively constructed as terrorist acts. By contrast, Al-Jazeera's narratives are congruent with the Middle Eastern perspectives and represent the operation as both a battle against occupation and a struggle for Palestinian independence. The study highlights the significance of media literacy in fostering critically engaged news media consumption and calls for more balanced perspectives in news coverage on international conflicts. It also underscores the value of employing diverse analytical approaches to deepen understanding of media representations in conflict contexts, thereby expanding on existing research in this particular field.